New Challenges, New Ideas: Shaping Education in 2025 - Beatriz Amante García (Journal of Technology and Science Education)
We begin a new year with great enthusiasm and changes at JOTSE. As is customary in our first editorial of the year, we will present the journal's progress and outline the challenges ahead.